An analysis on the impact of logistics on customer service - Francesco Querin; Martin Göbl (Journal of Applied Leadership and Management, 2017)
What is the connection between Logistics, customer service and customer Satisfaction levels? What are the role and importance of a Company's Logistics policies on the overall Customer Experience? What is a generally acceptable response time from a Customer Service?
Keywords: 650; Supply Chain Management; Supply Chain; Management; Logistics Management; Logistics; Customer; Customer Service; Customer Experience